A Analisis Dosis Paparan Radiasi Sekitar Ruang Pemeriksaan CT-Scan - Arafatillah, Siti (Progressive Physics Journal, 2025)
This thesis focuses on the analysis of radiation exposure around the CT-Scan room of Radiology Installation of Abdoel Wahab Sjahranie Samarinda Hospital. This study aims to determine the level of radiation exposure in the surrounding area and evaluate the level of exposure according to BAPETEN's safe limits. In addition, this thesis tries to identify areas with radiation potential that exceeds the safe limit and find out the cause. The research method includes data collection by direct measurement using a surveymeter. The results obtained show significant variations in exposure levels at each location. In the operator's room, the dose rate of 1.62 mSv/h exceeded the permissible limit for radiation workers, which was likely due to proximity to radiation sources and suboptimal protection. In the ultrasound room, the dose rate was 0.497 mSv/hour. This value is still below the controlled area limit but above the public safety limit of 0.1 mSv/hour. In the hallway, the measured dose rate was 0.462 mSv/hr which also exceeded the public limit, requiring access restrictions for the public. The garden area showed a dose rate of 0.604 mSv/hour, with high exposure for areas that may be accessed by the public. Therefore, practical recommendations include the addition of shielding, access restrictions, and installation of warning signs to reduce exposure in areas frequently accessed by the public.